Analisis Pengaruh Kemampuan Daya Serap dan Pembelajaran Organisasional pada Kemampuan Inovasi (Studi Empiris pada Usaha Mikro, Kecil, dan Menengah Binaan di Jayapura) - Irma Srem, Ade; F. Siwa, Siane (Jurnal Etnik: Ekonomi-Teknik, 2023)
The ability to innovate itself is not easy because it has complex risks and uncertainties in the market environment. The Resource Based View theory states that the most important organizational assets are knowledge and the two most important learning processes are exploitation and exploration. Both learning is said to be important because it can produce short-term and long-term performance. However, the exploitation process (utilization of existing knowledge) and the exploration process (utilization of new knowledge) are very difficult to manage simultaneously. Seeing the important role of MSMEs as described in their development, MSMEs are expected to make a positive contribution, especially in the economic sector. In general, MSMEs have less absorption power because the number of members is small, so the ability to create innovation is very difficult. On the other hand, MSMEs have a flexible organizational structure, reactive mentality, informal style, strong friendships, and dynamic strategies so that the absorption of knowledge can be realized effectively in exploitation and exploration activities. Based on the research inconsistencies obtained, this study aims to examine (1) the effect of absorptive capacity on organizational learning (exploitation and exploration), (2) absorptive ability on innovation ability, (3) organizational learning on innovation ability, and (4) the effect of organizational learning as a mediation in the relationship between absorptive capacity and innovation ability. The sample used in this study is Micro, Small and Medium Enterprises (MSMEs) in Jayapura. The analysis tool used is Structural Equation Modeling (SEM) Version 22 to test the hypothesis. The results showed that first, absorptive capacity had a positive effect on organizational learning (exploitation and exploration), second, absorptive capacity had a positive effect on innovation ability, third, organizational learning (exploitation and exploration) had a positive effect on innovation ability and fourth, organizational learning (exploitation and exploitation) as a mediation does not mediate the ability of absorption and innovation ability.